Kualitas Pelayanan Publik Kartu Tanda Penduduk Elektronik (E-KTP) - Isma, Yuli Santri; Aswad, Hajar; Teniro, Alwin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2023)
Public services are all activities carried out by an organization or agency in an effort to meet the needs of the community. This study aims to analyze the quality of public services in the making of e-KTP in the Population and Civil Registration Office of Bener Meriah Regency, Aceh Province and to determine the Supporting and Obstacles Factors in Service Quality in the Management of e-KTP at the Office of Population and Civil Registration Office of Bener Meriah Regency Aceh. The quality of public services in the Population and Civil Registry Office of Bener Meriah Regency is still considered to be less than optimal, this is due to the still poor indicators of service quality, namely: (1) Tangibles (bureaucratic), the Population and Civil Registration Office of Bener Meriah Regency has not yet met the service facilities adequate in providing quality public services in the management of e-KTP to the public. (2) Reliability, the results of the study show that the Population and Civil Registry Office of Bener Meriah Regency has delivered services quickly and on time. However, the processing time for e-KTP services is unclear, due to blank blanks and often problematic servers (3) Assurance, guarantees of service that cannot be expected due to the lack of timely service